1: -(5)^-1

A: -1/5
B: -5
C: 5 *****
D: 1/5

2; (-4.7) ^0
A: 1***
B: -1
C: 0
D: -4.7

3:
-1/p^-6
A: -6/p-6
B: -6p ****
C: -p^6
D: p^6

4: 6^3 x 6^10
A: 36^13
B: 6^13
C: 6^30 *****
D: 18^30

Simplify this expression (-4) ^-6 (-4) ^7
A: 4^13
B:-4 *****
C: 13
D: 1

3 answers

I just need it to be checked please.
#1 no
#2 yes
#3 no
#4 no
#5 yes

looks like somebody needs more review and exercises.
#1. negative exponents mean reciprocals.
-(5)^-1 = -(1/5) = -1/5
#2. ok
#3. again with the negative exponents...
-1/p^-6 = -1 / (1/p^6) = -1*p^6 = -p^6
You can think of negative exponents as switching a number between top and bottom of a fraction, and changing between plus and minus (the exponent only!)
x^-6 = x^06/1 = 1/x^6
1/y^2 = y^-2
1/y^-2 = y^2

#4. when multiplying numbers, add powers
6^3 x 6^10 = 6^13
It's just a shorthand way of writing 6*6*6 * 6*6*6*6*6*6*6*6*6*6 = 6^13
what you did was
(6^3)^10 = (6*6*6) ... 10 times = 6^30
you multiply the exponents when raising a power to a power

#5. correct
Though I wonder whether it was an accident, given your mistakes above. Too bad you didn't show any work ...